Kontribusi Penggunaan E-Learning sebagai Media Pembelajaran Online terhadap Hasil Belajar Sistem Komputer - Rina Wilda; M Menrisal; Rini Sefriani (JURNAL PTI (PENDIDIKAN DAN TEKNOLOGI INFORMASI) FAKULTAS KEGURUAN ILMU PENDIDIKAN UNIVERSITA PUTRA INDONESIA "YPTK" PADANG, 2021)
This study aims to determine the contribution of the use of e-learning as an online learning medium to the learning outcomes of class X computer systems at SMK N 2 Padang. This study also aims to test the proposed hypothesis. This type of research is quantitative using correlational research methods. This research was conducted at SMK N 2 Padang in the even semester. The population in this study were students of class X Computer Systems at SMK N 2 Padang. The sampling technique used is total sampling. And students who became the sample in this study amounted to 72 students. The instrument used in collecting data in this study were questionnaires and questions arranged according to the Likert scale model. Data analysis was carried out using SPSS 20. Based on the results of the study, the hypothesis of the rcount value is -0.028 while the rtable value is 0.232 because the rcount value is smaller than the rtable value (-0.028 > 0.232) which means that it can be interpreted that there is no positive relationship between the use of e-learning as a learning medium with student learning outcomes at a very low level of correlation coefficient.